O Programa Gira Mundo : a mobilidade estudantil internacional como ferramenta de inclusão social no Estado da Paraíba - Silva, Tulhio Cezidio Serrano da (2023)
This dissertation examines the Gira Mundo International Exchange Program, an initiative implemented in 2015 by the Government of the State of Paraíba through the State Department of Education, via the Executive Directorate of Student Development. The study aims to diagnose the profile of the beneficiaries of this student mobility policy in different regions of the state, identify its impacts, and analyze transformations in the teaching and learning process during the program's operation period, from 2016 to 2019.The theoretical and methodological construction stems from a reflection on international student mobility, grounded in the contributions of Teichler (2004, 2009), Aguiar (2017), and Prado (2000, 2002). The research is characterized as fieldwork, qualitative in nature, utilizing the focus group technique with student exchange participants from various regions of the state. According to Veiga & Gondim (2001), this approach is effective in understanding the perceptions, attitudes, and social representations of human groups.The analysis focuses on the experiences of students from the state public school system in Paraíba, providing answers regarding sociocultural and educational impacts during the program's execution. According to Teichler (2009), internationalization aims for mutual understanding, the enhancement of educational quality, a richer cultural life, and ultimately, economic growth.Results indicate that the Gira Mundo Program transcended geographical boundaries, reaching over 50% of the Paraíba territory in just four years. This outreach demonstrates not only the program's effectiveness but also its direct impact on diverse communities, promoting a more inclusive and globalized education. The "spill-over effect" is noteworthy, where students not only absorbed knowledge but also became active agents in disseminating this learning.The research also highlighted the development of youth leadership among the exchange participants, who not only absorbed academic lessons but became agents of change in their communities, serving as inspirational models for other young people. The methodology, including the focus group method, underscored the importance of innovative strategies in researching youth and education public policies. The study, aligned with robust theoretical principles, demonstrated that Gira Mundo not only transcended geographical boundaries but also shaped a more inclusive, global, and excellenceoriented educational culture throughout the state of Paraíba.In summary, the Gira Mundo Program emerges as a Paraíban revolution, leaving traces of impact across various educational and social domains. The research highlights the urgency of investing in education and the potential of youth as a transformative path, solidifying Education as the master key to a democratic, egalitarian, and fully developed society.